Pessimism and the secular problem of evil - Ruiters, Siphamandla (Rhodes University, Faculty of Humanities, Department of Philosophy)
How should we respond to the prevalence of ubiquitous evil? In this thesis, I present two responses to the secular problem of evil. The secular problem of evil exists because we want to live good lives, but we are all existentially vulnerable to evil. Consequently, we can think of various ways in which evil's existence poses a problem for us. When faced with such evil, I distinguish two responses that we may adopt, namely, optimistic or pessimistic responses to the secular problem of evil. These responses may be understood as stances that we may adopt about the relative evil and goodness in the world. Once I have made a thorough evaluation of the discussion around the secular problem of evil and the responses, I will suggest that pessimism is an appealing and appropriate response that we should adopt. To achieve the aims of this thesis, I will first clarify the kind of evil at stake in this thesis and then explain how philosophers have historically responded to this problem. Secondly, I will focus on the contemporary discussion on the secular problem of evil and show the responses are optimistic responses. Finally, I will provide a case against optimism and then show why pessimism is the most appealing and appropriate response.
Keywords: Good and evil; Pessimism; Optimism; Secularism; Quality of life